An Optimization of the Autoregressive Model Using the Grid Search Method - Tahyudin, Imam; Nambo, Hidetaka; Goto, Yoshitaka (International Journal of Engineering and Technology, 2018)
The purpose of this study is to find the parameters that can produce the best value on the model Autoregressive (AR). The parameter evaluation method used is the Maximum Likelihood Estimator (MLE) and using Grid Search optimization methods. The experimental data used in this study was a sunspot dataset. Based on our analysis, the best Autoregressive model was a 3rd order AR model.Â Â